Implementation of an ergonomics intervention in a Swedish flight baggage handling company—A process evaluation - Bergsten, E.; Mathiassen, Svend; Larsson, J.; Kwak, L. (Public Library of Science, 2018)
© 2018 Bergsten et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Objective To conduct a process evaluation of the implementation of an ergonomics training program aimed at increasing the use of loading assist devices in flight baggage handling. Methods Feasibility related to the process items recruitment, reach, context, dose delivered (training time and content); dose received (participants’ engagement); satisfaction with training; intermediate outcomes (skills, confidence and behaviors); and barriers and facilitators of the training intervention were assessed by qualitative and quantitative methods. Results Implementation proved successful regarding dose delivered, dose received and satisfaction. Confidence among participants in the training program in using and talking about devices, observed use of devices among colleagues, and internal feedback on work behavior increased significantly (p<0.01). Main facilitators were self-efficacy, motivation, and perceived utility of training among the trainees. Barriers included lack of peer support, opportunities to observe and practice behaviors, and follow-up activities; as well as staff reduction and job insecurity. Conclusions In identifying important barriers and facilitators for a successful outcome, this study can help supporting the effectiveness of future interventions. Our results suggest that barriers caused by organizational changes may likely be alleviated by recruiting motivated trainees and securing strong organizational support for the implementation.